OPPORTUNITIES OF POSITRON-EMMISION TOMOGRAPHY IN RADIATION THERAPY OF LUNG CANCER PATIENTS - Stolyarova, O.Yu.; Solodyannykova, O.I.; Kmetyuk, Ya.V. (World of Medicine and Biology, 2019)
In the group of patients with lung cancer, the possibilities of PET / CT-18F-FDG were studied to optimize the planning of radiation therapy. A comparative analysis of the advantages of metabolic image application to determine the size of radiation targets was carried out in order to focus the maximum radiation energy in the most functionally active tumor areas and to reduce side effects on healthy lung tissues. PET / KT-18F-FDG permits to optimize the planning of radiation process specifying the size of the irradiated target. The index of the tumor clinical volume, determined using PET-18F-FDG, is greater, and the value of the macroscopic volume intramodal variable is smaller compared to CT data. Analysis of the metabolic image permits predicting the nature of further radiation, bringing the radiation energy to the most functionally active part of the tumor, reducing the effect on healthy lung tissue, and as a result, reducing the incidence of radiation side effects and improving the quality of life in patients.